2020
DOI: 10.3390/mti4040075
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Nature Exposure and Test Anxiety

Abstract: The number of students affected by exam anxiety continues to rise. Therefore, it is becoming progressively relevant to explore innovative remediation strategies that will help mitigate the debilitating effects of exam anxiety. The study aimed to investigate whether green environment exposure, delivered by virtual reality (VR) technology, would serve as an effective intervention to mitigate participants’ test anxiety and therefore improve the experience of the exam, measured by positive and negative affect, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…There was a skew toward youth in most studies, with 70.8% of the subjects being under 30 years old and only one study specifically aimed at seniors (mean age: 72.7; Chan et al, 2021b ). Three studies included clinical populations who suffered from mild depression, stress, anxiety ( Jo et al, 2022 ), depressive symptoms ( Meuwese et al, 2021 ), or high exam anxiety ( O’Meara et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a skew toward youth in most studies, with 70.8% of the subjects being under 30 years old and only one study specifically aimed at seniors (mean age: 72.7; Chan et al, 2021b ). Three studies included clinical populations who suffered from mild depression, stress, anxiety ( Jo et al, 2022 ), depressive symptoms ( Meuwese et al, 2021 ), or high exam anxiety ( O’Meara et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study declared the use of a procedure to schedule random numbers (Meuwese et al, 2021). However, no apparent baseline differences were found between intervention groups except in one study (O'Meara et al, 2020). Thus, most studies that were unclear in randomization methods and the concealment of allocation sequence still received a "some concern" rating in the randomization process domain.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Generalized anxiety disorder (6/34, 18%) [ 27 , 28 , 39 , 42 , 46 , 49 ] was next, followed by public speaking anxiety (4/34, 12%) [ 14 , 31 , 51 , 56 ]. The rest of the studies aimed at specific clinical conditions such as paruresis [ 40 ], exam anxiety [ 48 ], driving-related [ 38 ] or car passenger anxiety [ 30 ], disruptive behavior in the classroom [ 45 ], or social anxiety in children with autism spectrum disorder [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…VR music therapy was used in the treatment of social anxiety in adolescents with autism spectrum disorder. Other interventions applied were VR games or exercises [ 15 , 45 , 46 , 49 ], CBT in addition to VR [ 14 , 27 , 38 , 39 ], and 360° VR videos [ 36 , 44 , 48 , 51 ]. Approximately 9% (3/34) of studies used different types of VR interventions, such as visuo-haptic–based multimodal feedback VR system [ 32 ], VR-based neurofeedback therapy [ 42 ], and a VR task-tracking avoidance behavior [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the study by Anderson et al [ 58 ] has shown that exposure to 360° videos of nature reduced negative affect in comparison to a control environment. Another study revealed that VR nature exposure improved negative affect in a sample of students who experienced exam anxiety [ 59 ].…”
Section: Discussionmentioning
confidence: 99%